A facile synthetic strategy for the creation of hollow noble metal/transition metal oxide nanocomposites. Issue 8 (8th January 2019) - Lin, Xi-Jie; Sun, Tian-Qi; Yang, Li-Ping; Sun, Yong-Gang; Bin, De-Shan; Duan, Shu-Yi; Liu, Yuan; Lv, Rong-Wen; Cao, An-Min
Abstract : An efficient synthetic strategy was developed for the preparation of various hollow noble metal/transition metal oxide nanocomposites. Abstract : We have reported an efficient synthetic protocol to build different hollow hybrid nanocomposites with tunable compositions, such as Au/TiO2, Pt/ZrO2, and Au/Ce x Ti1− x O2 . The noble metal nanoparticles were well encapsulated in a wall composed of the designated transition metal oxides, showing promising potential as stable catalysts as demonstrated by Pt/ZrO2 for methane combustion.